GEOLOGY AND STATIC CARBONATE RESERVOIR MODELLING OF BATURAJA FORMATION, SAFFRON FIELD, NORTH WEST JAVA BASIN - Dhiya Permana, Salma
Technology development and human growth increasing the demand of energy especially oil and gas. in contrast with the increasing of the demand, oil and gas production was decreased in the last 10 years. Therefore, optimization of oil and gas production is required. Saffron Field is a development oil field that located at the northern offshore of DKI Jakarta Province. Geologically, Saffron Field located at North West Java Basin which is Tertiary-aged basin. The purposes of this study are determining geological model and estimating remaining reserve from the reservoir. This study focused on Baturaja Formation consisting limestone as its lithology. Data used in this study are wireline log from 17 wells, seismic 3D, core description, side wall core description, and petrographic description. There are several methods used in this study, such as wells data analysis that consist of stratigraphic correlation, lithofacies analysis, electrofacies analysis, and petrophysics analysis; seismic data analysis that consist of seismic facies analysis, depth structure map determination, and isopach map determination; static reservoir modelling; fluid contact determination; and estimation of Original Oil In Place (OOIP). Lithofacies analysis based on core and petrographic description shows 5 lithofacies on research interval, they are Coral Floatstone (Cf), Foraminifera Grainstone – Packstone (Fgp), Skeletal Packstone (Sp), Foraminifera Packstone – Wackestone (Fpw), and Skeletal Wackestone – Mudstone (Swm). Those lithofacies composing a facies association which is platform interior (Restricted – Open Marine). Electrofacies and seismic facies analysis shows there is patch reef facies association that grow in platform interior. Both facies association composes platform interior as the depositional environment. Structural geology analysis shows normal fault system that have NE – SW trend which is associated with the horst system at the research area. Static reservoir modelling including structural, facies, and petrophysical modelling performed to determine the reservoir geometry, property distribution, and the estimation of hydrocarbon reserves. The estimation of Original Oil In Place (OOIP) from the reservoirs is 49 million stock tank barrels (MMSTB).